Investigation on the Mental Health Status of ICU Practitioners and Analysis of Influencing Factors During the Stable Stage of COVID-19 Epidemic in China - He, Wei; Chen, Wenjin; Li, Xiaopeng; Kung, Sui Sum; Zeng, Liangnan; Peng, Tangming; Wang, Xiaomeng; Ren, Reng; Zhao, Di (Frontiers in Public Health, 2021)
Objective: To understand the impact of COVID-19 epidemic on the mental health status of ICU practitioners in China, and to explore the relevant factors that may affect the mental health status of first-line medical workers. Methods: The study covered most of the provinces in China, and a questionnaire survey was conducted based on the WeChat platform and the Wenjuanxing online survey tool. With the method of anonymous investigation, we chose ICU practitioners to participate in the investigation from April 5, 2020 to April 7, 2020. The respondents were divided into two groups according to strict criteria of inclusion and exclusion: those who participated in the rescue work of COVID-19 (COVID-19 group) and those who did not (non-COVID-19 group). The SCL-90 self-evaluation scale was used for the evaluation of mental health status of the subjects. Results: A total of 3851 respondents completed the questionnaire and were included in the analysis. First, the overall mental health status of the investigated population, compared with the Chinese norm (n=1388), was reflected in 9 related factor groups of the SCL-90 scale, and significant differences were found in every factor in both men and women, except for the interpersonal sensitivity in men. Second, the overall mental health of the COVID-19 group was better than that of the non-COVID-19 group by the SCL-90 scale. Third, for the COVID-19 group, we have revealed several influencing factors for their mental health, and the statistical results showed that these factors had a significant influence on the mental health of the subjects in the COVID-19 group. Conclusion: The mental health status of the ICU practitioners in the COVID-19 group is better than that of the non-COVID-19 group, which could be attributed to a strenghened mentality and awareness of risks related to occupational exposure and enforced education on preventive measures for infectious diseases before being on duty.